Legal gaps under deregulatory broadband policies and the resurgent rise of corporate power - Barbara A. Cherry (International Telecommunications Society (ITS), 2011)
This paper considers the likely combinatorial effects of U.S. deregulatory broadband policies and the evolution of law as applied to corporations as a general matter. It explains how legal developments in both areas have dismantled bodies of law or doctrines that had developed to address corporate power in both commercial and political spheres and to protect consumers from vulnerability in commercial activities. Moreover, the coexistence of these developments enables an unprecedented transfer of corporate power between economic and policymaking institutions. With the decline in regulatory constraints, as well as the rise in constitutional rights to block attempts to impose regulatory constraints, there is a resurgent rise of corporate power. The result may be a phase transition undermining the rule of law so critical to sustainable democracies.
Keywords: K23; 330; Antitrust; broadband; common carriers; constitutional rights; consumer protection; corporations; telecommunications